Entry Regulation and Competition. Evidence from retail and labor markets of pharmacists. - Maximiliane Unsorg; Davud Rostam-Afschar (ZBW - Leibniz Information Centre for Economics, 2021)
We examine a deregulation of German pharmacists to assess its effects on retail and labor markets. Our theoretical model suggests that firms with high managerial efficiency open more stores per firm and have higher labor demand due to the reform. We find a sharp persistent increase in entry rates for expanding firms. These firms can double revenues but not profits after three years. We show that the increase of the number of employees by 50% after five years and the higher overall employment in the local markets, which increased by 40%, can be attributed to the deregulation.
Keywords: M1; J44; L4; L5; L2; J23; 330; regulation; acquisitions; entry; market concentration; wages; employment; pharmacists